Strategi Dinas Pemadam Kebakaran Kota Bekasi Dalam Menanggulangi Bencana Kebakaran Di Permukiman Padat Penduduk - Akhmad Khanza Akbar Bacas; Wahidin Septa Zahran (Jurnal Ilmu Administrasi Publik, 2022)
This study aims to find out about "The Strategy of the Bekasi City Fire Service in Overcoming Fire Disasters in Densely Populated Settlements". This study uses a descriptive qualitative analysis method to describe and explain in detail about existing phenomena using interview techniques as a supporting instrument. In this study, "The strategy of the Bekasi City Fire Department in Overcoming Fire Disasters in Densely Populated Settlements can be measured from 5 (five) strategy indicators, namely: Purposes, Environment, Direction, Action, Learning, data collection techniques used by means of observation, interviews, and documentation. Data analysis techniques are data reduction, data presentation and drawing conclusions. The informants of this study totaled 5 people. It can be concluded that the Strategy of the Bekasi City Fire Service in Tackling Fire Disasters in Densely Populated Settlements